(untitled) (Journal of Hama University, 2020)
This study aimed to identify the impact of the application of the principles of governance in the profitability ratios of banks listed in the Damascus securities market, the problem of the study is the existence of some shortcomings in the application of the rules of governance in the banks listed in the Damascus securities market and the extent of the relationship between them and the increase in the profitability ratios >These banks by examining two ratios of profitability return assets (ROA) and the return on Shareholders ’ rights (ROE). To achieve the objectives of the study, the descriptive approach was followed, based on the published reports and financial statements, as well as the bank governance reports under the supervision of the Syrian Securities and Markets Authority covering the period of time from 2010 to 2016 that addressed the subject of Governance and financial performance of banks. The governance data were extracted from corporate governance reports under the supervision of the Syrian Securities and Exchange authority, and data were emptied, monitored, tabulated and entered using Excel, and the weight/1/ was given to the applicable and partially applied governance rule and weight/0/ of the governance base Not applied, the financial ratios for measuring the performance of banks from the Damascus Stock Exchange website were extracted from the existing annual reports of each bank, and then statistical analyses were carried out using the Social Sciences statistical Package (SPSS) programme, and the percentage of application was relied upon Principles of governance in banks Study hypotheses were tested using the one way anova variance analysis. He then presented the mechanism used in applying the principles of governance by some Syrian banks and their role in improving profitability and then analyzing and interpreting the results and identifying the possibility of circulating them. This study concludes with a series of findings, the most important of which are: 1- There is a moral difference to the impact of the application of the principle of shareholders ’ rights at the low and intermediate level in the return on assets (ROA) for banks listed on the Damascus Securities Exchange. 2-There is a moral difference to the effect of applying the principle of disclosure and transparency at a good level rather than applying it at an average level of return on assets (ROA) for banks listed on the Damascus Securities Exchange. 3-There is a moral difference to the effect of applying the principle of the board of directors at a good level rather than applying it at a low or moderate level in the return on Shareholders ’ rights (ROE) for banks listed on the Damascus Securities Exchan ge.